Transaction Arrangements and Quality Management Strategies in British-Brazilian Fruit TradeTransaction Arrangements and Quality Management Strategies in British-Brazilian Fruit Trade - Carvalho, José Márcio (2003)
Faculdade de Economia, Administração, Contabilidade e Gestão de Políticas Públicas (FACE)